2021
DOI: 10.1126/sciadv.abe0974
|View full text |Cite
|
Sign up to set email alerts
|

The structure of enteric human adenovirus 41—A leading cause of diarrhea in children

Abstract: Human adenovirus (HAdV) types F40 and F41 are a prominent cause of diarrhea and diarrhea-associated mortality in young children worldwide. These enteric HAdVs differ notably in tissue tropism and pathogenicity from respiratory and ocular adenoviruses, but the structural basis for this divergence has been unknown. Here, we present the first structure of an enteric HAdV—HAdV-F41—determined by cryo–electron microscopy to a resolution of 3.8 Å. The structure reveals extensive alterations to the virion exterior as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 69 publications
5
59
0
Order By: Relevance
“…The penton base protein folds into two domains: a single jellyroll and an upper insertion facing the solvent-exposed exterior ( Figure 2 b) [ 44 , 51 ]. This upper domain contains the hypervariable loop, which due to its flexibility, has not been traced in any of the available HAdV structures [ 7 , 27 , 29 , 30 , 51 ]. In most human adenoviruses, the hypervariable loop bears the RGD sequence, an α v integrin-binding motif.…”
Section: Structure Of the Capsid Proteinsmentioning
confidence: 99%
See 3 more Smart Citations
“…The penton base protein folds into two domains: a single jellyroll and an upper insertion facing the solvent-exposed exterior ( Figure 2 b) [ 44 , 51 ]. This upper domain contains the hypervariable loop, which due to its flexibility, has not been traced in any of the available HAdV structures [ 7 , 27 , 29 , 30 , 51 ]. In most human adenoviruses, the hypervariable loop bears the RGD sequence, an α v integrin-binding motif.…”
Section: Structure Of the Capsid Proteinsmentioning
confidence: 99%
“…This disordered part is absent in Atadenoviruses, which have a shorter penton base protein and also lack the mobile, variable loops on the outer surface, as observed for the hexon HVRs [ 31 ]. Comparison of a high-resolution structure of recombinant HAdV-F41 penton base with the same protein in the context of the virion has shown that regions of the protein involved in interactions with the peripentonal hexons, fiber, and protein IIIa are disordered in solution, but become ordered upon capsid assembly [ 27 ]. Virus-like particles can be formed by penton base pentamers of certain HAdV species assembling in dodecahedra, with uses in receptor identification, gene delivery, and vaccine development [ 55 ].…”
Section: Structure Of the Capsid Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike most other HAdVs, which can infect cells of multiple organs, enteric HAdVs exclusively infect the intestinal tract and do not cause any infections at other sites. We recently showed that this restricted tropism can be attributed to differences in the external structure of the virion as compared to respiratory and ocular HAdVs [28]. The restricted tropism has also been suggested to depend on the ability of the SF of HAdV-F40 and HAdV-F41 to protect the virus against acidic gastric conditions [29,30].…”
Section: Introductionmentioning
confidence: 99%